Effectiveness of Office Administration in Licensing Services in Pesaku Village, West Dolo District, Sigi Regency - Suasa, Suasa; Haryono, Dandan (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research aims to determine and analyze the effectiveness of licensing administration in Pesaku Village, West Dolo District, Sigi Regency. This research uses a qualitative approach with in-depth interview techniques, focus group discussions (FGD), participant observation, and document analysis. Informants were selected from the Pesaku Village community who actively use licensing services. Based on research results, the effectiveness of Pesaku Village licensing services is still low. Achievement oisimely services, contribution to the vision and mission, and community satisfaction are still below the targets set. Service capacity is also not optimal and not yet responsive to community needs. From the dimensions of objectives, systems and multiple constituents, the effectiveness of licensing services in Pesaku Village still needs improvement. There is a need to increase human resource capacity, innovate service systems, and listen more and respond to community input.